2020
DOI: 10.21203/rs.2.13812/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the short-term disease recurrence after Loop Electrosurgical Excision Procedure (LEEP)

Abstract: Background The goal of cervical cancer screening is to identify dysplastic lesions for subsequent excision in order to prevent invasive disease. There is clinical equipoise, on how to best follow women for disease surveillance after treatment with some Canadian provinces exclusively performing colposcopy and some utilizing HPV testing in addition to cervical cytology. Loop Electrosurgical Excision Procedure (LEEP) is used to treat pre-invasive HPV-mediated disease and patients are typically followed for 12 mon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In our cohort, approximately half of patients have abnormal results among those who underwent a LEEP for persistent low-grade or HPV positivity over a follow-up period of approximately 2 years, which is not significantly altered by whether occult high grade was identified on the LEEP specimen. This rate of abnormal cytology and/or hrHPV positivity is slightly higher than reported in literature 9–11 but nevertheless suggests that intense surveillance is needed for these patients, likely akin to those who underwent LEEP for high-grade dysplasia. Possible reasons for higher rate of abnormal cytology and/or hrHPV positivity on follow-up are the consistent use of HPV-based testing for surveillance at our center, the intentional use of small LEEPS in this population to prevent future adverse reproductive outcomes, and selection bias by patients who opt to follow up with their local gynecologist and would have only returned to our center if abnormal testing was identified.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In our cohort, approximately half of patients have abnormal results among those who underwent a LEEP for persistent low-grade or HPV positivity over a follow-up period of approximately 2 years, which is not significantly altered by whether occult high grade was identified on the LEEP specimen. This rate of abnormal cytology and/or hrHPV positivity is slightly higher than reported in literature 9–11 but nevertheless suggests that intense surveillance is needed for these patients, likely akin to those who underwent LEEP for high-grade dysplasia. Possible reasons for higher rate of abnormal cytology and/or hrHPV positivity on follow-up are the consistent use of HPV-based testing for surveillance at our center, the intentional use of small LEEPS in this population to prevent future adverse reproductive outcomes, and selection bias by patients who opt to follow up with their local gynecologist and would have only returned to our center if abnormal testing was identified.…”
Section: Discussionmentioning
confidence: 53%
“…In terms of counseling patients with persistent low-grade abnormalities, it is important to note that our risk of positive margins in this study is higher than generally reported in the literature for LEEPs performed for women undergoing LEEPs for biopsy-proven HSIL (5%–20%) 9–11 . This is intentional, as we counsel patients in the group undergoing LEEP for persistent low-grade abnormalities that we will intentionally do a small “diagnostic” LEEP so as to remove as little cervix as possible while “ruling out” an occult high-grade diagnosis, when the diagnosis is uncertain, as it is known that smaller excisions are less likely to result in adverse pregnancy outcomes, and we want to limit the amount of tissue removed.…”
Section: Discussionmentioning
confidence: 96%